PENINGKATAN PENGETAHUAN DAN SIKAP GIZI SEIMBANG ANAK SEKOLAH DASAR MELALUI MEDIA PERMAINAN EDUKASI “ZIPLOCK GAMES” - Almunawa, Iqlima; Rosmana, Dadang; Priawantiputri, Witri; Mulyo, Gurid Pramintarto Eko (Poltekkes Kemenkes Bandung, 2024)
Based on the 2018 Basic Health Research Data, it was found that the prevalence of nutritional problems in School Age Children (AUS) was in the fairly high category for the short (16.9%), thin (6.8%), overweight (9.2%) and obese (10,8%). Delivery of health information to school-age children requires media that is easy to understand and attracts children's attention so that information can be conveyed properly. This study aims to determine the effect of the educational game